Beetroot juice — a suitable post-marathon metabolic recovery supplement?. Issue 1 (3rd December 2021) - Stander, Zinandré; Luies, Laneke; van Reenen, Mari; Howatson, Glyn; Keane, Karen M.; Clifford, Tom; Stevenson, Emma J.; Loots, Du Toit
Abstract: Background: Red beetroot ( Beta vulgaris L. ) is a multifunctional functional food that reportedly exhibits potent anti-inflammatory, antioxidant, vasodilation, and cellular regulatory properties. This vegetable has gained a fair amount of scientific attention as a possible cost-effective supplement to enhance performance and expedite recovery after physical exercise. To date, no study has investigated the effects of incremental beetroot juice ingestion on the metabolic recovery of athletes after an endurance race. Considering this, as well as the beneficial glucose and insulin regulatory roles of beetroot, this study investigated the effects of beetroot juice supplementation on the metabolic recovery trend of athletes within 48 h after completing a marathon. Methods: By employing an untargeted two-dimensional gas chromatography time-of-flight mass spectrometry approach, serum samples (collected pre-, post-, 24 h post-, and 48 h post-marathon) of 31 marathon athletes that ingested a series ( n  = 7; 250 ml) of either beetroot juice ( n  = 15 athletes) or isocaloric placebo ( n  = 16 athletes) supplements within 48 h post-marathon, were analysed and statistically compared. Results: The metabolic profiles of the beetroot-ingesting cohort recovered to a pre-marathon-related state within 48 h post-marathon, mimicking the metabolic recovery trend observed in the placebo cohort. Since random inter-individual variation was observed immediately post-marathon, only metabolites with large practical significance ( p -value ≤0.05 and d -value ≥0.5) within 24 h and 48 h post-marathon were considered representative of the effects of beetroot juice on metabolic recovery. These ( n  = 4) mainly included carbohydrates (arabitol and xylose) and odd-chain fatty acids (nonanoate and undecanoate). The majority of these were attributed to beetroot content and possible microbial fermentation thereof. Conclusion: Apart from the global metabolic recovery trends of the two opposing cohorts, it appears that beetroot ingestion did not expedite metabolic recovery in athletes within 48 h post-marathon.